The Explicit Construction of Einstein Finsler Metrics with Non-Constant Flag Curvature - Guo, E.; Mo, X.; Zhang, X. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
By using the Hawking Taub-NUT metric, this note gives an explicit construction of a 3-parameter family of Einstein Finsler metrics of non-constant flag curvature in terms of navigation representation.